PENGETAHUAN DAN PEMANFAATAN METODE PENGOBATAN TRADISIONAL PADA MASYARAKAT DESA SUKA NALU KECAMATAN BARUS JAHE - SALMEN SEMBIRING (Departemen Sosiologi Universitas Sumatera Utara, 2012)
ABSTRACT Every society has its own way to meet their needs, including the needs of health. These methods are essentially inherited from generation to generation to the next generation so that it becomes a local knowledge. Such knowledge would survive if people still believe in and utilize that knowledge. In this case the knowledge of the methods of traditional medicine in the village of Karo District, Suka Nalu Kecamatan Barus Jahe. Therefore, the authors sought to determine the methods and forms of utilization.The research method used is descriptive method with qualitative research studies. How to get data by observation, in-depth interviews, and library research. The unit of analysis and the informants in this study is the peoples in Suka Nalu. The data obtained from the observations, interviews, and interpreted based support literature as reference deduce conclusions. The method of treatment is known by the community, among other methods of treatment with herbs are eaten or drunk, methods of treatment using the herb acts or actions, and methods of treatment that combined treatment with an edible herb or drunk and with action. The forms use traditional treatment methods that exist in the community that is as natural resource use environmentally friendly, treat yourself, family members, neighbors and others or as a source of additional income for traditional healers. (Keyword: Local knowledge, methods of treatment, traditional medicine, utilization)